"American Dream" or Global Nightmare? - Melanie E. L. Bush (Journal of Global Initiatives, 2010)
In the United States we are witnessing a period of heightened contestation about the parameters of nationalism, patriotism, and loyalty. The oft-heard phrase "Support the Troops" now signifies the desire both to send more soldiers to war and to bring home those already in combat. This "nation of immigrants" has spawned a new generation of "minute-men" to defend national borders while mainstream discourse touts the benefits of "diversity." Dreams of upward mobility present for some during the mid-20th century seem now hazy at best as the proportional income of those at top grows while the rest of the population increasingly struggles. In this context, this article explores related transitions in notions of "nation" and who "belongs."